فعالية برنامج إرشادي في خفض أعراض الاكتئاب لدى أمهات الأطفال ذوي الشلل الدماغي - شرف الدين، إيناس عمرو أحمد وهبة; السيد، ماجدة إبراهيم أحمد; راضي، فوقية محمد محمد (جامعة المنصورة - كلية التربية, 2021)
هدف البحث الحالي إلى التحقق من فعالية برنامج إرشادي في خفض أعراض الاكتئاب لدى أمهات الأطفال ذوي الشلل الدماغي، تكونت عينة الدراسة من (٢٠) أما من أمهات الأطفال ذوي الشلل الدماغي بمركز طيبة للعلاج الطبيعي في طلخا بمدينة المنصورة محافظة الدقهلية بمصر تم تقسيمهن بالتساوي إلى مجموعتين: تجريبية وضابطة، وتمثلت أدوات الدراسة في مقياس "بيك" للاكتئاب، وبرنامج إرشادي (إعداد الباحثة)، وتوصلت نتائج الدراسة إلى وجود فروق دالة إحصائيا بين متوسطي رتب درجات الأمهات في المجموعة التجريبية والمجموعة الضابطة في القياس البعدي على مقياس الاكتثاب لصالح المجموعة الضابطة، كما توصلت نتائج الدراسة إلى وجود فروق دالة إحصائيا بين متوسطي رتب درجات الأمهات في المجموعة التجريبية في القياسين القبلي والبعدي على مقياس الاكتئاب لصالح القياس القبلي، بينما توصلت نتائج الدراسة إلى عدم وجود فروق دالة إحصائيا بين متوسطي رتب درجات الأمهات في المجموعة التجريبية في القياسين البعدي والتتبعي على مقياس الاكتئاب، كما تبين وجود حجم تأثير مرتفع للبرنامج الإرشادي في خفض أعراض الاكتئاب لدى الأمهات في المجموعة التجريبية، وقد أوصت الباحثة باستخدام البرنـامج الإرشادي المستخدم في الدراسة الحالية لخفض أعراض الاكتئاب لدى أمهات الأطفال ذوي الاحتياجات الخاصة.
The present study aimed to investigate the effectiveness of a counseling program in reducing depression symptoms in mothers of children with cerebral palsy. The study sample consisted of (20) mothers of children with cerebral palsy referred from Taibah Center for Physical Therapy in Talkha city, Dakahlia Governorate, Egypt, divided into two equivalent groups: Experimental and control. Study instruments implied Beck Depression Scale and a Counseling Program (prepared by the researcher). The study results revealed statistically significant differences between the mean ranks of the experimental and control groups in the posttest on Beck Depression Scale in favor of the control group. The study results also revealed statistically significant differences between the mean ranks of the pre and posttests on Beck Depression Scale in favor of the pretest. Whereas the study results revealed no statistically significant differences between the mean ranks of the post and follow up test on Beck Depression Scale. The results showed high effect size of the program in reducing depression symptoms in mothers of children with cerebral palsy in the experimental group as well. The researcher recommended using the counseling program used in the present study for reducing depression symptoms in mothers of children with special needs.
Keywords: الأطفال -- الشلل الدماغي -- الأمهات -- الضغوط النفسية -- الاكتئاب -- البرامج الإرشادية -- مدينة المنصورة -- مصر